Economic strategies for the development and modernization of water transport infrastructure (Economics and region, 2022)
The article summarizes the regulatory and legal requirements for the development of strategic programs for the development of the national transport system, regional and sectoral transport complexes, water transport enterprises and business entities that carry out auxiliary activities in the field of maritime and inland water transport. Systematized and provided a critical assessment of the program documents of the state, which define economic strategies for the development and modernization of water transport infrastructure. The target targets of strategies for the development and modernization of water transport infrastructure are proposed, the main of which are: privatization under the condition of limiting state ownership of strategic objects and natural-monopoly segments; attraction of private investors and operators for operation of infrastructure facilities based on concession mechanisms; creation of conditions for implementation of public-private partnership projects; improvement of service for consumers of transport services in the field of internal and external transportation; coordination of port capacity and corresponding port infrastructure; growing role of sea and river ports in serving international supply chains, multimodal and intermodal transportation. A hierarchical approach to the formation of the economic policy of development and modernization of water transport infrastructure based on the synthesis of multi-level strategies is substantiated: first, the state level (National Transport Strategy of Ukraine); secondly, the sectoral level (Strategy for the development of seaports of Ukraine, Strategy for the development of inland water transport of Ukraine); thirdly, the territorial level (State strategy of regional development); fourthly, the level of economic entities carrying out auxiliary activities in the field of sea and inland water transport. It is shown that the quality of the developed strategies and the effectiveness of the practical implementation of their provisions depends on the effectiveness of communication links vertically (branch subordination) and horizontally (regional transport complexes), as well as the degree of coordination of interests of interested parties.
Keywords: economic strategies; development; modernization; infrastructure; water transport